Chikungunya Virus in the Americas — What a Vectorborne Pathogen Can Do - Staples, J. Erin; Fischer, Marc (The New England journal of medicine, 2014)
As of early August, more than half a million cases of chikungunya virus infection had been reported in the Americas. The rapid spread is probably attributable to a lack of population immunity and the broad distribution in the Americas of vectors capable of transmitting the virus. In December 2013, the first local transmission of chikungunya virus in the Western Hemisphere was reported, beginning with autochthonous cases in Saint Martin. Since then, local transmission has been reported in 31 countries or territories throughout the Americas, including locations in the United States and its territories (Florida, Puerto Rico, and the U.S. Virgin Islands) (see figure). As of August 8, 2014, a total of 576,535 suspected and laboratory-confirmed chikungunya cases had been reported in the Americas, a case count that had nearly doubled over the previous month (see interactive graphic, available with the full text of this article at . . .